THE EFFECT OF ORGANIZATIONAL CULTURE, WORK MOTIVATION, AND JOB SATISFACTION ON THE PERFORMANCE ACCOUNTING TEACHER IN THE SOUTH JAKARTA - Subekti, Elok; Zulaihati, Sri; Sumiati, Ati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine the effect of organizational culture, work motivation and job satisfaction on the performance of accounting teachers in South Jakarta. The data testing technique uses multiple linear regression analysis which produces the equation Ẏ = 3.845 + 0.367X1 + 0.322X2 + 0.384X3. The results of the analysis based on the t test and f test show: (1) There is a positive and significant influence between organizational culture and teacher performance. (2) There is a positive and significant influence between work motivation and teacher performance. (3) There is a positive and significant influence between job satisfaction and teacher performance. (4) There is a positive and significant influence between organizational culture, work motivation and job satisfaction on teacher performance. Based on the results of this analysis, it can be concluded that organizational culture, work motivation and job satisfaction simultaneously affect teacher performance.